The Relationship between Maternal Characteristics, Toddlers and Compliance to the Posyandu with the Nutritional Status of Toddlers at the Padang Serai Health Center, Bengkulu City, 2023 - Wulandari, Retno Ajeng; Samidah, Ida; Sari, Lezi Yovita (Student Scientific Journal, 2024)
Toddlers are the age group that most often suffers from malnutrition and malnutrition, which can be assessed by measuring nutritional status. Nutritional status of toddlers is closely related to various factors including mother's age, mother's education level, parents' occupation, total family income, child characteristics and the regularity of mothers checking their children to the health service unit. This study aims to determine the relationship between the characteristics of mothers, toddlers and compliance to come to Posyandu with the nutritional status of toddlers at the Padang Serai Health Center, Bengkulu City in 2023.This research method is observational research using a cross sectional study approach and this research design is focused on knowing the factors of maternal characteristics, toddlers and compliance with coming to Posyandu that affect the nutritional status of toddlers with a total sample of 87 samples with a purposive sampling method then conducted interviews and filling out questionnaires by parents / mothers of toddlers and then measuring nutritional status based on anthropometric measurements of BB / UU compared to WHO_NCHS Z-score values. The results of the univariate test analysis of respondents who had toddlers with good nutritional status were 78 respondents (89.3%) while respondents who had toddlers with poor nutritional status were 9 respondents (10.3%). Bivariate analysis results There is no relationship between the characteristics of mothers, toddlers and the level of compliance of maternal visits to posyandu with the nutritional status of toddlers at the Padang Serai Health Center, Bengkulu City in 2023.Researchers suggest that the health center can provide useful information and input in efforts to improve health services for mothers and children, especially in providing counseling to mothers related to posyandu and nutritional status in toddlers.